Crossing disciplinary boundaries: An ethnographic exploration of academic publishing invitations. - Severinsen C (Taylor and Francis Group, 2024)
Background: This autoethnographic study examines email invitations for health researchers to publish in journals outside their expertise, exploring implications for interdisciplinary research and knowledge production. Methods: Over three months, email invitations to publish outside the author’s field were documented and analysed thematically and through reflexive journaling. Results: Five main themes in publication invitations were identified: emphasising novelty, promising rapid publication, appealing to research impact, flattering language, and persistent messaging. Reflexive analysis revealed complex factors shaping responses, including publication pressures, desires for prestige, and tensions between disciplinary norms and interdisciplinary collaboration. While invitations may present opportunities for novel collaborations, they often reflect predatory publishing practices. Conclusions: Navigating this landscape requires careful discernment, commitment to academic integrity, and reflexivity about one’s positionality. The study underscores the need for researchers to critically interrogate the motivations behind such invitations. Further research could explore decision-making processes across disciplines and implications for academic publishing integrity and equity.
Keywords: Publication ethics; academic pressures; academic publishing; autoethnography; decision-making; interdisciplinary; research integrity